Yodium Plant (Jatropha multifida Linn.) Leaf Extract Reduces Bleeding Time - Waseso, Wahyu; Mahmudah, Nur; Jatmiko, Safari Wahyu; Dewi, Listiana Masyita (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Bleeding is a physiological response to vascular injury; however, prolonged bleeding time may indicate impaired hemostatic function. Various medicinal plants have been traditionally used to accelerate wound healing and control bleeding. One such plant is the yodium plant (Jatropha multifida Linn.), which is widely utilized in traditional medicine due to its potential hemostatic and anti-inflammatory properties. The bioactive compounds contained in its leaves are believed to contribute to the enhancement of blood coagulation and the reduction of bleeding duration. This study aimed to determine the effect of Jatropha multifida Linn. leaf extract on bleeding time. This study employed an experimental design to evaluate the effect of Jatropha multifida Linn. leaf extract on bleeding time. The subjects were divided into control and treatment groups. The treatment group received Jatropha multifida leaf extract, while the control group did not receive the extract. Bleeding time was measured after the intervention to assess the hemostatic effect of the extract. The collected data were analyzed to compare bleeding time between the groups. The results demonstrated that the administration of Jatropha multifida Linn. leaf extract was associated with a reduction in bleeding time compared with the control group. This finding suggests that the extract possesses hemostatic potential, which may be attributed to the presence of bioactive compounds that support the blood clotting process. Jatropha multifida Linn. leaf extract has the potential to reduce bleeding time, indicating its possible role as a natural hemostatic agent.Keywords: Jatropha multifida; leaf extract; bleeding time; hemostatic effect; medicinal plants